Taking “anak emas” system (MyAnakEmas) to the cloud - Ahmad Dahlan, Abdul Rahman (2012)
This conceptual paper seeks to put forth a novel vision, namely the combined deployment of Quadruple Helix Model (QHM) collaboration mooted by Agensi Inovasi Malaysia, “whole-of-government” concept of ICT implementation across the Malaysian government agencies mooted by MAMPU, and the advances in cloud computing that can be used to set up what is known as of “Anak Emas” System or MyAnakEmas. The QHM actors, namely the Government, Academia, Industry and Citizen need to collaborate and share resources in nurturing and addressing the needs of less privileged and less fortunate children including orphans holistically, rather than the current practice executed in silos, isolation or independently. This proposed collaborative inter-organizational MyAnakEmas is to enable a consolidated approach for government agencies, NGOs, private sector and individuals in building up a single and trusted national database on “Anak Emas” or orphanage children. This database, owned and managed by a government agency such as Jabatan Kebajikan Masyarakat, can be used and updated by all other authorized and relevant organizations and individuals in making a consolidated contribution in nurturing and developing these orphanage children to be independent and developing entrepreneurship culture from an early age. Thus, eliminating duplication in data, efforts and investments made by various organizations. At the same time, enhancing timely decision-making based on quality, single and trusted view on “Anak Emas”.